The wine headache: consumer perceptions, marketing, and pricing implications for non-sulfited wines - Appleby, Christopher, author; Costanigro, Marco, author; Thilmany-McFadden, Dawn, author; Colorado State University, Department of Agricultural and Resource Economics, publisher (Colorado State University. Libraries, 2012)
This report covers the following ke points for the wine industry: A considerable share of consumers believe that sulfites in wine cause headaches; Consumers reporting headaches after moderate wine consumption are particularly receptive to low-sulfite wine marketing assurances; Consumers are willing to pay a small premium for low-sulfite wines, but only if it does not com-promise quality levels. Marketing opportunities may be particularly attractive to smaller producers if they determine small batch production methods result in reduced wine spoilage risks.
Keywords: low-sulfite; headaches; sulfites; wine consumption; wine industry